Gender-Related Effects of Sex Steroids on Histamine Release and FcεRI Expression in Rat Peritoneal Mast Cells - Samira Muñoz-Cruz; Yolanda Mendoza-Rodríguez; Karen E. Nava-Castro; Lilián Yepez-Mulia; Jorge Morales-Montor (Journal of Immunology Research)
Mast cells (MCs) are versatile effector and regulatory cells in various physiologic, immunologic, and pathologic processes. In addition to the well-characterized IgE/FcεRI-mediated degranulation, a variety of biological substances can induce MCs activation and release of their granule content. Sex steroids, mainly estradiol and progesterone, have been demonstrated to elicit MCs activation. Most published studies have been conducted on MCs lines or freshly isolated peritoneal and bone marrow-derived MC without addressing gender impact on MC response. Our goal was to investigate if the effect of estradiol, progesterone, testosterone, and dihydrotestosterone (DHT) on MCs may differ depending on whether female or male rats are used as MCs donors. Our results demonstrated that effect of sex steroids on MCs histamine release is dose- and gender-dependent and can be direct, synergistic, or inhibitory depending on whether hormones are used alone or to pretreat MCs followed by substance P-stimulation or upon IgE-mediated stimulation. In contrast, sex steroids did not have effect on the MC expression of the IgE high affinity receptor, FcεRI, no matter female or male rats were used. In conclusion, MCs degranulation is modulated by sex hormones in a gender-selective fashion, with MC from females being more susceptible than MC from males to the effects of sex steroids.